Competency Assessment in Problem-Based Learning Projects of Information Technologies Students - Agnė BRILINGAITĖ; Linas BUKAUSKAS; Anita JUŠKEVIČIENĖ (Informatics in Education, 2018)
The rapid development of new technologies requires a new set of skills from all users in operating, using, and maintaining digitised environments. Curriculum design in the field of Information and Communication Technologies (ICT) undergoes a rapid change as technological achievements do influence education. The aim of the article was to present research results on the mappings of learning outcomes to taxonomies to evolve from requirement-based assessment to competency-based assessment. The research was carried out on the problem-based learning (PBL) module. The article presents a novel PBL model design with activities and evaluation schema. The developed model could be used to guide the curricula design of information technologies for generic competencies, and to foster skills essential for the future ICT sector.